Implementing Case-Method in Maritime-Related Learning: A Qualitative Descriptive Study in Physics Learning on The Topic of Hydrostatics Pressure - Sarkity Dios; Liana Metta; Fitriani Rita; Sundari Putri Dwi (BIO Web of Conferences)
The need to develop 21st-century skills requires lecturers to apply appropriate learning to develop skills. This study aims to describe how the implementation of case-method learning for physics lectures on the topic of hydrostatic pressure by integrating the maritime context. This research is a descriptive study. The approach used in this study is a qualitative approach. Data collection was carried out through observation and documentation. Data were analyzed descriptively and presented based on the stages of case- method learning. The implementation of the case method in physics learning on the topic of hydrostatic pressure by linking the maritime context can be done by providing problems that are in accordance with the conditions or events that students often encounter. For instance, we present a problem related to the sinking of the KRI Nanggala 402 ship, a real-life maritime incident involving a steel ship that split into 3 parts. Students discuss in groups to find solutions to problems using appropriate physics concepts and strategies. After going through a series of problem-solving processes, students can understand the essence of the concept of hydrostatic pressure, what events are related to this concept, and how to apply it in solving problems.